Experience of parents who have suffered a perinatal death in two Spanish hospitals: a qualitative study - Marcos Camacho-Ávila; Cayetano Fernández-Sola; Francisca Rosa Jiménez-López; José Granero-Molina; Isabel María Fernández-Medina; Laura Martínez-Artero; José Manuel Hernández-Padilla (BMC, 2019)
Abstract Background Perinatal grief is a process that affects families in biological, psychological, social and spiritual terms. It is estimated that every year there are 2.7 million perinatal deaths worldwide and 4.43 deaths for every 1000 births in Spain. The aim of this study is to describe and understand the experiences and perceptions of parents who have suffered a perinatal death. Methods A qualitative study based on Gadamer's hermeneutic phenomenology. The study was conducted in two hospitals in the South of Spain. Thirteen mothers and eight fathers who had suffered a perinatal death in the 5 years prior to the study participated in this study. In-depth interviews were carried out for data collection. Inductive analysis was used to find themes based on the data. Results Eight sub-themes emerged, and they were grouped into three main themes: 'Perceiving the threat and anticipating the baby's death: "Something is going wrong in my pregnancy"'; 'Emotional outpouring: the shock of losing a baby and the pain of giving birth to a stillborn baby'; "We have had a baby": The need to give an identity to the baby and legitimise grief'. Conclusion The grief suffered after a perinatal death begins with the anticipation of the death, which relates to the mother's medical history, symptoms and premonitions. The confirmation of the death leads to emotional shock, characterised by pain and suffering. The chance to take part in mourning rituals and give the baby the identity of a deceased baby may help in the grieving and bereavement process. Having empathy for the parents and notifying them of the death straightaway can help ease the pain. Midwives can help in the grieving process by facilitating the farewell rituals, accompanying the family, helping in honouring the memory of the baby, and supporting parents in giving the deceased infant an identity that makes them a family member.